Filles victimes, filles vicieuses, filles dangereuses - Hélène Duffuler-Vialle (Criminocorpus)
Society's view of the minor prostitute oscillates between pity and fear. This ambiguity was reinforced in the 19th and 20th centuries by a legal paradox. The young girl, an official victim of prostitution, is in fact legally apprehended as dangerous and seized in the criminological discourse as vicious.The 1910 International Convention aims to protect young girls from international trafficking. A few cases of trafficking, extracted from the National and Departmental Archives of the North, show that there is indeed a prostitution-related emigration, but that the young girls involved in this trafficking have multiple trajectories that are not free of empowerment. The statistics on pimping litigation show that these cases are rare, which is out of step with the over-mediatization of the phenomenon. The gap between the facts and their media coverage is obvious. The anxiety-provoking context of trafficking allows for a global control by the social body of women's sexuality and their attempts at emancipation. Paradoxically, these facts are also instrumentalized by the feminist press itself. The aims are different: to fight against regulation and even to support other feminist causes.At the national level, a penal policy to combat the prostitution of minors has existed since the beginning of the 19th century. At the end of the 19th century, the legislator no longer hesitated to introduce himself into the family sphere to control the education given to children by parents, with the possible sanction of deprivation of the rights of paternal power, especially if the child prostitutes himself. In 1935, it was not so much a question of punishing the failing parent as of introducing educational supervision measures. The 1908 Civil Law aims to protect young people from prostitution. It implements so-called "preservation" measures. The criminal law of 1921 reveals a coercive penal policy by assimilating vagrancy and prostitution of minors. These protective or coercive laws have the same purpose: the confinement of minors who are prostitutes. The aim is not so much to protect them as to protect society from the health and social risks of this particularly disturbing street prostitution. In addition to the law, municipal bylaws regulate and organize health surveillance of youth prostitution. At the same time, the 19th century criminological theories of the Italian positivist school (Lombroso, Ferri, Garofalo) and the French School of Social Anthropology (Lacassagne, Tarde) combined gave birth during the inter-war period to the School of Modern Anthropology founded by Doctor Vervaeck. The study on minors by Paul-Jean Cogniart in 1938 is in line with this new trend and offers an analysis of the psychological problems of young girls, their family environment and the exogenous causes of their prostitution. His study serves to justify and reinforce regulation and leaves aside the image of the "victim", however spearheading abolitionism in the public debate, an image that will officially supplant that of the vicious girl after the Second World War, while remaining topical in stereotypes about prostitution.The ambiguities and paradoxes noted in the discourses of the public authority (legislator, judge and criminologist) show that the minor prostitute is clearly a deviant "bad girl", even a delinquent one. The mobilized victim discourse serves only as a pretext for framing the sexuality of young girls and women more broadly.